Pengembangan Kebijakan Pendidikan Islam Berbasis Kearifan Lokal - Triyatni; Ahmad Subagyo; Muhamad Sofian Hadi; Ahmad Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the development of Islamic education policies based on local wisdom values. Islamic education, which has traditionally been normative, often overlooks local socio-cultural aspects. This research uses a descriptive qualitative approach through literature review and document analysis. The findings indicate that integrating local wisdom into Islamic education policies can strengthen students' character, develop contextual Islamic identities, and foster a more holistic educational system. Therefore, the development of Islamic education policies based on local wisdom is crucial for creating an education system that is relevant to the community context.